Peningkatan Kreativitas Anak Usia Dini Melalui Cerita Bergambar pada Anak Didik di TK Pertiwi Metro - Azizah, Hanifah Fitria (Indonesian Research Journal on Education, 2022)
Children's creativity needs to be improved, therefore learning must be interesting and fun. One way to increase creativity is through picture stories. This study aims to determine the increase in children's creativity through picture stories. This research is a classroom action research. The subjects in this study were students of group B2 TK of the State Kindergarten, the second semester of the 2020/2021 academic year. The number of students in the B2 TK group of the coaches is 25 children. This research is collaborative between researchers, school principals, and accompanying class teachers. Data were collected through observation, field notes, interviews, and documentation. The validity of the data waschecked by triangulation. The data were analyzed descriptively and qualitatively by the flow model. The results of this study indicate that there is an increase in children's creativity through picture stories, namely pre-cycle creativity by 13.33%, increasing creativity in cycle I by 46.67% and increasing creativity in cycle II reaching 80.00%. To increase children's creativity through picture stories, it is also supported by several indicators, namely creative reactions, long attention span, self-organization / selfconfidence, linking ideas or ideas / storytelling, developing imagination and adding new vocabulary. In addition, success in increasing creativity is also supported by supporting methods such as giving time toexplore and giving motivation in the form of very good. The conclusion of this study is that picture stories can increase children's creativity.